The influence of cavity size and location within insulation paper on the Partial Discharge activities - Roslan, Muhammad Hakirin; Azis, Norhafiz; Ab Kadir, Mohd Zainal Abidin; Jasni, Jasronita; Mohd Yousof, Mohd Fairouz (UPM Press, 2023)
This paper examines the influence of cavity size and location in the insulation paper on the Partial Discharge (PD) activities through Finite Element Method (FEM). The model consisted of a conductor wrapped with insulation paper. Two different locations of the spherical cavities were introduced in this study, namely Location 1 (L1) and Location 2 (L2), located at the center and left corner of the insulation paper. The model introduced two different sizes of cavities with diameters of 0.5 mm and 0.8 mm. An AC voltage source of 17 kV, 50 Hz, was applied at the conductor while the bottom of the insulation paper was grounded. The real and apparent PDs were obtained by integrating the current flowing through the cavity and ground electrode with the respective surface area. The simulation was carried out for 100 cycles. The resultant model was used to study the PD occurrence, magnitude, and Phase Resolved Partial Discharge (PRPD) within the insulation paper. It is found that the large cavity size produces a lower number of PD occurrences per cycle than the small cavity size. The large cavity size produces a higher charge magnitude as compared with the small cavity size. The PD occurrence per cycle and charge magnitude are higher for the cavity location at L1 compared to L2. The PRPD yields the same pattern for cavity location at L1 and L2, whereby the differences are only on the charge magnitude and PD occurrence per cycle.